(untitled) (Revista Venezolana de Salud Pública, 2020)
The activities of human beings and their interaction with the environment as an adaptation process, these relationships have resulted in public health problems, due to land degradation, water scarcity, and zoonotic diseases, these are produced by the contact of an animal infected with the pathogenic species bacteria, parasites, viruses and fungi, between humans, animals and their environment causing endemics, epidemics and pandemics, in this case wild rabies is direct transmission through the mucosa of the eyes, nose, mouth or skin cut by the virus of the Rhabdoviridae family, due to ecological changes resulting from the interaction of these microorganisms, causing complex incidents affecting the most vulnerable population, causing great economic losses and serious damage to health public. In this context, the purpose of this study is to know rabies in Lara state, as it is an endemic state to wild rabies, the source of information was taken from the National Institute of Comprehensive Agricultural Health and the review of reports, for which it will be developed a description of its evolution and behavior from the period 2007-2019, for this reason this information is of great importance because it allows to have a historical count of positive cases for rabies in Lara state as a contribution that will contribute to the understanding of the illness.